Ethical responsibilities of man toward animal world. The vision of Robert Spaemann - Kożuchowski, Józef (Studia Ecologiae et Bioethicae, 2020)
The article presents the concept of moral obligations that man has towards animals proposed by Robert Spaemann. Spaemann give reasons for perceiving animal as an object of the law. His analyses present possibilities of solving basic moral questions like for example experiments on animals, animal husbandry, animal slaughter, hunting, interfering into animal's nature and our responsibility for them. Spaemann presents very original arguments for taking care of and responsibility for animals, deriving it from human dignity.